Redox‐Active Vanadium‐Based Polyoxometalate as an Active Element in Resistive Switching Based Nonvolatile Molecular Memory. Issue 18 (6th August 2020) - N. S., Sterin; Basu, Nivedita; Cahay, Marc; M. N., Satyanarayan; Mal, Sib Sankar; Das, Partha Pratim
Abstract : Resistive switching (RS)‐based random access memory has been envisaged as a viable alternative to existing memory technology due to its nonvolatility, high switching speed, high endurance/retention, and considerably low operating voltage. Herein, a new uniform, repetitive, and stable RS phenomenon is demonstrated based on very low‐cost two‐terminal metal–insulator–metal stack fabricated using a highly redox‐active vanadium‐based polyoxometalate (POM) molecular clusters, [V10 O28 ] 6− —belonging to polyoxovanadate (POV) family. The RS is observed to be unipolar and nonvolatile in nature, and occur at a fairly low operating bias voltage (less than 2 V), making it suitable for low‐power operations. The switching event is attributed to the cycling between formation and rupture of tiny conductive nanofilaments formed due to trapping and detrapping of positively charged ionized oxygen vacancy sites present in the active switching layer of [V10 O28 ] 6− . POMs, in their rich abundance, are highly stable early transition‐metal oxide nanosized clusters, capable of storing as well as releasing a large number of electrons. In addition, they can undergo fast and reversible redox reactions (both in solid and liquid electrolyte media) in "stepwise" manner—a property that makes them a promising candidate for ultrafast and multi‐level nonvolatile molecular memory for high‐density data storage. Preliminary investigations on the POV‐based memory cells result in device resistance ratio ≈25, endurance for more than 200 cycles, and stable retention time around 2200 s, in fully open air condition. Abstract : Highly redox‐active vanadium‐centric polyoxometalate (POM) clusters are exploited for building ultrafast and nonvolatile molecular memory. POMs are large reservoir of electrons and they can undergo fast reduction–oxidation process through electron delocalization around its molecular cage. The results presented here demonstrate the ability of POMs as an active element to fabricate resistive random‐access memory (RRAM) for high‐density data‐storage applications.